2006
DOI: 10.1128/jvi.80.7.3666-3669.2006
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Evidence for the Rapid Evolution of Human B19 Erythrovirus

Abstract: Human B19 erythrovirus is a ubiquitous viral pathogen, commonly infecting individuals before adulthood. As with all autonomous parvoviruses, its small single-stranded DNA genome is replicated with host cell machinery. While the mechanism of parvovirus genome replication has been studied in detail, the rate at which B19 virus evolves is unknown. By inferring the phylogenetic history and evolutionary dynamics of temporally sampled B19 sequences, we observed a surprisingly high rate of evolutionary change, at app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
114
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 20 publications
16
114
1
2
Order By: Relevance
“…Especially during the initial phase of B19V infection, characterized by high levels of viral replication, there might be a greater chance of appearance of inaccurately replicated B19V DNA; although, the viral DNA is replicated by the host cell machinery. It has been recently speculated by others (Ló pez-Bueno et al, 2003;Shackelton & Holmes, 2006) that the fidelity and the proofreading activity of the enzymic complex containing the host DNA polymerase, recruited cellular replication factors and the viral NS1 protein may not be as efficient in single-stranded DNA viruses as expected so far. Furthermore, it has been demonstrated that B19V, similar to parvoviruses infecting animals, has a high rate of evolutionary changes that is more typical of RNA viruses (Ló pez- Bueno et al, 2006;Shackelton et al, 2005;Shackelton & Holmes, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially during the initial phase of B19V infection, characterized by high levels of viral replication, there might be a greater chance of appearance of inaccurately replicated B19V DNA; although, the viral DNA is replicated by the host cell machinery. It has been recently speculated by others (Ló pez-Bueno et al, 2003;Shackelton & Holmes, 2006) that the fidelity and the proofreading activity of the enzymic complex containing the host DNA polymerase, recruited cellular replication factors and the viral NS1 protein may not be as efficient in single-stranded DNA viruses as expected so far. Furthermore, it has been demonstrated that B19V, similar to parvoviruses infecting animals, has a high rate of evolutionary changes that is more typical of RNA viruses (Ló pez- Bueno et al, 2006;Shackelton et al, 2005;Shackelton & Holmes, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently speculated by others (Ló pez-Bueno et al, 2003;Shackelton & Holmes, 2006) that the fidelity and the proofreading activity of the enzymic complex containing the host DNA polymerase, recruited cellular replication factors and the viral NS1 protein may not be as efficient in single-stranded DNA viruses as expected so far. Furthermore, it has been demonstrated that B19V, similar to parvoviruses infecting animals, has a high rate of evolutionary changes that is more typical of RNA viruses (Ló pez- Bueno et al, 2006;Shackelton et al, 2005;Shackelton & Holmes, 2006). Since the NS1 gene evolves at a similar rate as the gene for VP2, it was suggested that immune selection is not the primary cause of the high substitution rate in B19V.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, high mutation rates (ca. 10 Ϫ4 ) have been reported for parvoviruses (35,64,65) and circoviruses (6,21). Like geminiviruses, these viruses have ssDNA genomes that replicate via rolling-circle mechanisms.…”
mentioning
confidence: 99%
“…In order to prove that mutation happened on high concentration of spectinomycin, the 16S rDNA of a green shoot which resists 500 mg l -1 spectinomycin was sequenced, resulting in a novel mutation site was found as shown in Figure 3. It is widely accepted on human diseases study that there is a strong correlation between selective pressure and the nucleotide substitution rate for distinct virus genes (Shackelton & Holmes, 2006;Shackelton et al, 2005). For example, capsid proteins of porcine parvovirus (PPV) interact with the host immune system.…”
Section: Evolution Of Chloroplast 16s Ribosome Rna Dependent Spectinomentioning
confidence: 99%